The Effect of Health Education on Childbirth on Third Trimester Primigravida Anxiety in Public Health Center Matiti in Humbang Hasundutan District 2022 - Retno Wahyuni; Udur Hotlan Maria Sianturi (Institute of Computer Science (IOCS), 2022)
he first pregnancy for a mother (primigravida) is one of the crisis periods in her life. In the third trimester (28-40 weeks), anxiety before the birth of a primigravida mother will appear. Pregnant women who experience anxiety during pregnancy will increase the risk of maternal emotional imbalance after giving birth. Anxiety that occurs continuously in pregnant women has an impact on infants and pregnant women such as placental abruption, low birth weight, the risk of delayed fetal motor and mental development, colic in newborns and prematurity. This study aims to determine the effect of providing health education about childbirth to third trimester primigravida anxiety. This quasi-experimental study used a pre and post test without control method with purposive sampling technique which was conducted on 17 third trimester primigravida pregnant women at health centers Matiti, Humbang Hasundutan District. Anxiety was measured using the HARS (Hamilton Anxiety Rating Scale) questionnaire. The results showed a decrease in anxiety scores between before and after treatment (p = 0.000). So it can be concluded that the provision of health education about childbirth with the lecture method can reduce the anxiety of third trimester primigravida pregnant women in facing childbirth. the results of this study suggest that research related to other interventions that may have an effect on reducing anxiety in third trimester primigravida pregnant women should be conducted.